Використання іноземного досвіду реінтеграції військовослужбовців - Твердохлєбова, Наталя Євгеніївна (Харківський національний університет внутрішніх справ, 2026)
Статтю присвячено аналізу та систематизації зарубіжного досвіду адаптації військовослужбовців до мирного життя й обґрунтуванню можливостей його імплементації в український контекст з урахуванням сучасних викликів, спричинених повномасштабною війною. Проаналізовано провідні міжнародні моделі підтримки ветеранів: американські програми Warrior PATHH, K9s for Warriors, Comprehensive Soldier and Family Fitness, ізраїльські практики YaHaLOM, Peace of Mind, NATAL, британські ініціативи Combat Stress, PTSD Resolution, Bravehound, які демонструють системність, міжвідомчу взаємодію та мультидисциплінарний підхід. Порівняльний аналіз виявив спільні закономірності, серед яких акцент на ранньому втручанні, використанні моделей «рівний – рівному» (peer-support), залученні родин і громад, а також науково обґрунтованому моніторингу ефективності програм. Визначено, що бойовий досвід українських військовослужбовців має унікальні характеристики, зумовлені тривалістю, інтенсивністю, високотехнологічним характером війни. Запропоновано модель програми комплексної допомоги українським військовим ветеранам, у межах якої передбачено інтеграцію доказових і комплементарних методів терапії, розвиток національної мережі підтримки, створення центрів обслуговування за принципом «єдиного вікна» (one-stop-shop), залучення сімей і громад до процесу відновлення, впровадження цифрових рішень для забезпечення доступності допомоги. Практична значущість дослідження полягає в можливості впровадження запропонованої моделі в систему надання допомоги ветеранам України, що сприятиме підвищенню ефективності реабілітаційних програм, зміцненню соціальної стабільності та відновленню людського потенціалу держави. Новизна дослідження полягає в розробленні адаптованої до українських реалій концепції багаторівневої підтримки ветеранів, заснованій на синтезі світових практик і національного досвіду. Результати можуть бути використані для формування державної політики у сфері соціальної та психологічної реінтеграції військовослужбовців, а також для розроблення спеціалізованих освітніх і тренінгових програм для фахівців системи підтримки ветеранів.

The article is devoted to the analysis and systematisation of foreign experience in adapting military personnel to civilian life and justifying the possibilities of its implementation in the Ukrainian context, taking into account the current challenges caused by full-scale war. Leading international models of veteran support are analysed: the American programmes Warrior PATHH, K9s for Warriors, Comprehensive Soldier and Family Fitness, Israeli practices YaHaLOM, Peace of Mind, NATAL, British initiatives Combat Stress, PTSD Resolution, Bravehound, which demonstrate consistency, interagency cooperation and a multidisciplinary approach. A comparative analysis has revealed common patterns, including an emphasis on early intervention, the use of peer-support models, the involvement of families and communities, and scientifically based monitoring of programme effectiveness. It has been determined that the combat experience of Ukrainian military personnel has unique characteristics due to the duration, intensity, and high-tech nature of the war. A model programme for comprehensive assistance to Ukrainian military veterans has been proposed, which provides for the integration of evidence-based and complementary therapy methods, the development of a national support network, the creation of one-stop-shop service centres, the involvement of families and communities in the recovery process, and the implementation of digital solutions to ensure the accessibility of assistance. The practical significance of the study lies in the possibility of implementing the proposed model in the system of assistance to veterans in Ukraine, will contribute to improving the effectiveness of rehabilitation programmes, strengthening social stability and restoring the human potential of the state. The novelty of the study consists in the development of a concept of multi-level support for veterans adapted to Ukrainian realities, based on a synthesis of global practices and national experience. The results can be used to shape state policy in the field of social and psychological reintegration of military personnel, as well as to develop specialised educational and training programmes for specialists in the veteran support system.
Using foreign experience in reintegrating military personnel
Keywords: реінтеграція ветеранів; міжнародний досвід; психологічна реабілітація; соціальна інтеграція; комплексна модель; посттравматичне зростання; модель "рівний – рівному"; мультидисциплінарний підхід; reintegration of veterans; international experience; psychological rehabilitation; social integration; comprehensive model; post-traumatic growth; peer to-peer model; multidisciplinary approach